1992
DOI: 10.1128/iai.60.4.1455-1464.1992
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis virulence in mice: induction of immunity to bacterial components

Abstract: Selected cell envelope components of Porphyromonas gingivalis were tested in a BALB/c mouse model in an attempt to elucidate further the outer membrane components of this putative oral pathogen that might be considered as virulence factors in host tissue destruction. Lipopolysaccharide (LPS), outer membrane, and outer membrane vesicles of P. gingivalis W50, ATCC 53977, and ATCC 33277 were selected to examine an immunological approach for interference with progressing tissue destruction. Mice were actively immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
96
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 46 publications
0
96
0
Order By: Relevance
“…Microorganisms and mouse infection P. gingivalis FDC 381 was cultured and maintained for the animal infections, which were initiated within 15-30 min of bacterial preparation, as described previously (Kesavalu et al, 1992) in studies showing that P. gingivalis induces an inflammatory infiltrate, osteoclast activation, and increased messenger RNA (mRNA) expression of proinflammatory cytokines in calvarial tissues (Zubery et al, 1998;Kesavalu et al, 2002). P. gingivalis was injected at 1.5 · 10 9 cells (n = 10) into the soft tissues overlying the calvaria of the mice.…”
Section: Animalsmentioning
confidence: 99%
“…Microorganisms and mouse infection P. gingivalis FDC 381 was cultured and maintained for the animal infections, which were initiated within 15-30 min of bacterial preparation, as described previously (Kesavalu et al, 1992) in studies showing that P. gingivalis induces an inflammatory infiltrate, osteoclast activation, and increased messenger RNA (mRNA) expression of proinflammatory cytokines in calvarial tissues (Zubery et al, 1998;Kesavalu et al, 2002). P. gingivalis was injected at 1.5 · 10 9 cells (n = 10) into the soft tissues overlying the calvaria of the mice.…”
Section: Animalsmentioning
confidence: 99%
“…The bacteria were washed three times with PBS and then heat killed at 801C for 10 min. (Kesavalu et al 1992). Using a spectrophotometer, the bacterial concentrations were standardized to an optical density of 0.1 at 650 nm, which corresponds to 10 10 CFU/ml (Baker et al 1994).…”
Section: The In Vivo Local Inflammation Modelmentioning
confidence: 99%
“…Many investigations have been designed to study the virulence of several oral pathogens and their role in the aetiology of periodontal disease. Most of them involved mono-infection animal models (Kesavalu et al 1992, Genco et al 1998, Baker et al 2000. Several studies have shown that co-infection with different pathogens modulates the immune response and affects the clinical outcome of the infection in various diseases (Vitovec et al 2001, Stoicov et al 2004).…”
mentioning
confidence: 99%